2019
DOI: 10.1073/pnas.1820567116
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic insights into mechanoactivation of focal adhesion kinase

Abstract: Focal adhesion kinase (FAK) is a key signaling molecule regulating cell adhesion, migration, and survival. FAK localizes into focal adhesion complexes formed at the cytoplasmic side of cell attachment to the ECM and is activated after force generation via actomyosin fibers attached to this complex. The mechanism of translating mechanical force into a biochemical signal is not understood, and it is not clear whether FAK is activated directly by force or downstream to the force signal. We use experimental and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 38 publications
3
89
0
Order By: Relevance
“…The crystals were obtained without any nucleotide added; however, an additive ( p ‐coumaric acid) was resolved in the ATP‐binding site. As we suspected, and is true for other kinases, 27 ATP/MgCl 2 binding stabilizes the kinase domain by 4°C (Figure 3b). Adding MgCl 2 without ATP may also have an effect on stability, which will be tested in future studies.…”
Section: Discussionsupporting
confidence: 72%
“…The crystals were obtained without any nucleotide added; however, an additive ( p ‐coumaric acid) was resolved in the ATP‐binding site. As we suspected, and is true for other kinases, 27 ATP/MgCl 2 binding stabilizes the kinase domain by 4°C (Figure 3b). Adding MgCl 2 without ATP may also have an effect on stability, which will be tested in future studies.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, unfolding of the ATP loaded kinase domain was observed only above 50 pN, hence even peak forces in focal adhesions do not result in FAK deactivation. In order to obtain an atomic view of FAK stretching, experimental pulling of FAK by AFM was correlated to corresponding force-probe molecular dynamics simulations performed via the same attachment points [88]. Overall simulations agreed well with experiments, with FERM-kinase detachment occurring prior to any FAK unfolding over a range of loading rates.…”
Section: Structural Aspects Of Force Mediated Fak Activationmentioning
confidence: 64%
“…In agreement with such a scenario, vinculin is shown to move away from the membrane towards the actin regulatory layer during myosin II mediated focal adhesion maturation [87]. Further, using atomic force microscopy (AFM) based single molecule force spectroscopy, it was shown that forces applied to FAK molecules via the KAKTLRK lipid binding site in the FERM domain and the C-terminus of the kinase domain (the FAT domain was not included in these studies) results in rupture of autoinhibitory interactions between the FERM and kinase domain [88]. A force peak observed only with wild-type FAK but not the constitutively open mutant of FAK was observed at 25 pN using a retraction speed of the AFM cantilever of 12,800 nm/s.…”
Section: Structural Aspects Of Force Mediated Fak Activationmentioning
confidence: 99%
“…For other proteins, as for example in focal adhesions, which are assumed to bear force‐regulatory functions our technique can help to characterize them by providing both biochemical and biomechanical information. [ 32,33 ] Our drift correcting, automated workflow, allows for measuring several days without interruption. This enables probing of an even larger number of ZMWs and will thus further improve statistical power.…”
Section: Resultsmentioning
confidence: 99%